Hormonally controlled ILC antigen presentation potential is reduced during pregnancy. Issue 1 (July 2020) - Einenkel, Rebekka; Ehrhardt, Jens; Hartmann, Kristin; Krüger, Diana; Muzzio, Damián Oscar; Zygmunt, Marek
Abstract : Strategically located in mucosal barriers, innate lymphoid cells (ILCs) are relevant in local containment and tolerance of commensal microflora. ILCs have been recently described at the fetomaternal interface, where the development of a semi-allogeneic fetus can only succeed in a well-controlled immune environment. We postulate that ILCs adapt their antigen presentation capacity to protect pregnancy from excessive immune responses. Human ILCs were studied in deciduae of term pregnancies, peripheral blood and in in vitro generated ILCs. Fresh isolated lymphocytes or cells treated with pregnancy-related factors were investigated. The fetal antigen rejection-based CBA/J × DBA/2J mouse model (poor outcome pregnant mice; POPM) was used to characterize ILC antigen presentation potential in normal and immunologically disturbed pregnancies. ILC antigen presentation potential was characterized by flow cytometry and qPCR. We discovered that the distribution of ILC subsets changed during both human and murine pregnancy. Moreover, the pregnancy was accompanied by reduced MHCII expression in splenic ILCs during normal pregnancy (CBA/J × BALB/c; good outcome pregnant mice; GOPM) but increased in splenic and intestinal ILCs of CBA/J × DBA/2J mice. In vitro, splenic ILCs from pregnant mice increased MHCII expression after stimulation with IL-1β and IL-23. In contrast, uterine ILCs displayed lower MHCII expression, which remained unchanged after stimulation. Finally, pregnancy-related factors and hormones present in the uterine environment reduced antigen presentation potential of human ILCs in vitro . Together, these data indicate that, during pregnancy, peripheral and especially uterine ILCs adapt their antigen presenting potential to maintain a level of tolerance and support pregnancy.